양극성 장애 환자의 낙인 저항에 대한 영향 요인 - 강성혁, 김우정, 송윤주, 김재민, 남궁기, 하규섭, 조현상 (Singyŏng chŏngsin ŭihak, 2015)
Objectives ZZStigma resistance is an individual capacity to fight the stigma of mental illness and is an issue of ongoing research regarding the stigma. The aim of this study was to evaluate predictors of stigma resistance in patients with bipolar disorder. MethodsZZDemographic, clinical, and psychosocial data were collected from 102 bipolar patients in a university mental hospital. Stigma resistance was measured using a subscale of the Internalized Stigma of Mental Illness Scale. Patients completed self-reported questionnaires including items on self-esteem, hopelessness, social support, and social conflict. ResultsZZStigma resistance showed positive association with functioning, self-esteem, and social support, and showed negative association with depressive symptoms, hopelessness, and social conflict. In multivariate analysis, stigma resistance was predicted by sex, education, and self-esteem. Self-esteem was the strongest predictive factor of stigma resistance. ConclusionZZIn accordance with previous studies, self-esteem was a central role of predicting stigma resistance. A program for improving self-esteem and its related psychosocial factors will be helpful to enhancing stigma resistance in bipolar patients. KCI Citation Count: 0